2019
DOI: 10.1109/comst.2018.2873950
|View full text |Cite
|
Sign up to set email alerts
|

The Long Road to Computational Location Privacy: A Survey

Abstract: The widespread adoption of continuously connected smartphones and tablets developed the usage of mobile applications, among which many use location to provide geolocated services. These services provide new prospects for users: getting directions to work in the morning, leaving a check-in at a restaurant at noon and checking next day's weather in the evening are possible right from any mobile device embedding a GPS chip. In these location-based applications, the user's location is sent to a server, which uses … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(67 citation statements)
references
References 130 publications
0
61
0
4
Order By: Relevance
“…LPAuditor offers a comprehensive analysis of the privacy loss caused by location metadata by also exploring whether the remaining locations can be used to infer personal information that is typically considered sensitive. While the inference of sensitive information has been one of the main motivations behind prior research on location-privacy [61], such automated attacks have not been demonstrated in practice. Our system examines tweets that place the user at (or in close proximity of) locations that are associated with such information.…”
Section: Introductionmentioning
confidence: 99%
“…LPAuditor offers a comprehensive analysis of the privacy loss caused by location metadata by also exploring whether the remaining locations can be used to infer personal information that is typically considered sensitive. While the inference of sensitive information has been one of the main motivations behind prior research on location-privacy [61], such automated attacks have not been demonstrated in practice. Our system examines tweets that place the user at (or in close proximity of) locations that are associated with such information.…”
Section: Introductionmentioning
confidence: 99%
“…A major technique widely used for showing amount of privacy is k‐anonymity. () It states that at least k‐1 other users should have the same property as the one which the user is exposing (POI in our work). As the framework we are working on is a collection of mobiles transferring data between themselves using WiFi, they cannot be too far from each other because no communication will be achieved if they are far.…”
Section: Resultsmentioning
confidence: 98%
“…Diante deste fato, diversas técnicas de proteçãoà privacidade têm sido propostas, como os algoritmos de anonimização baseados em pseudônimos. Um pseudônimoé um mecanismo de proteção a privacidade que consiste em substituir dados reais e sensitivos por identificadores que não tenham nenhuma associação com estes dados reais (Primault et al, 2018). Por exemplo, durante a publicação dos dados de localização de um veículo, as informações sensíveis como as placas dos veículos são substituídas por identificadores com o intuito de desassociar a identidade real do veículo 1 .…”
Section: Mix-zones: Um Esquema De Proteçãoà Privacidadeunclassified
“…A re-identificaçãoé uma das abordagens de ataqueà privacidade que parte do princípio de identificar trajetórias anonimizadas e, consequentemente, conhecer as identidades a partir de um conjunto limitado de informações sobre a entidade-alvo (Primault, Boutet, Mokhtar, & Brunie, 2018). Esseé um ataque que também pode ser a "porta de entrada" para outros que têm como alvo uma entidade específica.…”
Section: Introductionunclassified